Impact of Redox Condition on Fractionation and Bioaccessibility of Arsenic in Arsenic-Contaminated Soils Remediated by Iron Amendments: A Long-Term Experiment - Quan Zhang; Lixin Pei; Chunyan Liu; Mei Han; Wenzhong Wang (Geofluids)
Iron-bearing amendments, such as iron grit, are proved to be effective amendments for the remediation of arsenic- (As-) contaminated soils. In present study, the effect of redox condition on As fractions in As-contaminated soils remediated by iron grit was investigated, and the bioaccessibility of As in soils under anoxic condition was evaluated. Results showed that the labile fractions of As in soils decreased significantly after the addition of iron grit, while the unlabile fractions of As increased rapidly, and the bioaccessibility of As was negligible after 180 d incubation. More labile fractions of As in iron-amended soils were transformed into less mobilizable or unlabile fractions with the contact time. Correspondingly, the bioaccessibility of As in iron-amended soils under the aerobic condition was lower than that under the anoxic condition after 180 d incubation. The redistribution of loosely adsorbed fraction of As in soils occurred under the anoxic condition, which is likely ascribed to the reduction of As(V) to As(III) and the reductive dissolution of Fe-(hydr)oxides. The stabilization processes of As in iron-amended soils under the anoxic and aerobic conditions were characterized by two stages. The increase of crystallization of Fe oxides, decomposition of organic matter, molecular diffusion, and the occlusion within Fe-(hydr)oxides cocontrolled the transformation of As fractions and the stabilization process of As in iron-amended soils under different redox conditions. In terms of As bioaccessibility, the stabilization process of As in iron-amended soils was shortened under the aerobic condition in comparison with the anoxic condition.